Implementasi Nilai Moderasi Beragama pada Mata Pelajaran Pendidikan Islam Sebagai Basis Pengembangan Karakter Anak didik di Tumbuh High School - Bagus Mahardika (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2024)
This research is motivated by the need to teach the values of religious moderation at the senior secondary education level as a response to the phenomenon of spiritual understanding in some groups of Indonesian society who tend to be extreme. Considering that at the upper secondary education level, we are entering an age that is vulnerable to influences both from within and outside education. Therefore, it is important to internalize the objectives of this research, especially in the Growing High School environment. If not, a qualitative approach with a field study research design will gradually lead to national instability. Data was obtained through observation, interviews and documentation of actual conditions and facts occurring in the field, supported by books, current journals and other sources of related information. Data analysis was carried out by condensation, presentation and verification. The implementation of religious moderation is carried out using 4 strategies, namely, First, inserting moderation content in every lesson. Second, optimizing the learning approach. Third, organizing programs, education, training and special provisions. Fourth, the teacher makes observations simultaneously. The implementation of religious moderation in the Grow High School environment is already underway, realized in textbooks for subjects that are integral and interconnected, starting from regulations to levels of learning